Dear Freedom Writer : stories of hardship and hope from the next generation - Gruwell, Erin (Crown, 2022)
"The students of today tell their stories of adversity and growth in letters to the #1 New York Times bestselling authors of The Freedom Writers Diary--featuring powerful responses from the original Freedom Writers. Over twenty years ago, Erin Gruwell's first-ever class of high school students in Long Beach, California was labeled 'unteachable'--but she saw past that. Instead of treating them as scores on a test, she understood that each of them had a unique story to tell. Inspired by books like Anne Frank's diary, her students began writing their own diaries, eventually dubbing themselves the Freedom Writers. Together, they co-authored The Freedom Writers Diary, which launched a movement that remains incredibly relevant and impactful today. Their stories speak to young people who feel as if those around them do not care about their lives, their feelings, and their struggles. They want to be heard; they want to be seen. In Dear Freedom Writer, the next generation of Freedom Writers shares their struggles with abuse, racism, discrimination, poverty, mental health, imposed borders, LGBTQIA+ identity, and police violence. Each story is answered with a letter of advice from an original Freedom Writer. Writing with empathy and honesty, they answer these young people not with the platitudes of a politician or celebrity, but with the pragmatic advice of people who have dealt with these same issues and come out on the other side. Through its eye-opening and inspiring stories, Dear Freedom Writer paints an unflinchingly honest portrait of today's youth and offers a powerful message of perseverance, understanding, and hope"--